The Role of Spirituality and Religion for The Character Education of The Digital Generation - Alfons Seran (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
This research aims to discuss the role of spirituality and religion for the character education of the digital generation. In line with the purpose of national education as mandated in the Preamble to the 1945 Constitution, it is to educate the life of the nation by developing the potential of students so that they become a generation of the nation with character and professionalism. The character of the Indonesian nation, which is known for being friendly, polite, and noble ethics, is now starting to fade and be replaced by the character of violence, dishonesty, discrimination, bullying, hate speech and hoaxes. On the other hand, the Indonesian nation seems to be so religious. Places of worship are often seen full of worshippers. The digital generation lives in a social condition where ethical and moral values are not in line with the behaviors of their society. In this case, spirituality and religion can make a meaningful contribution to character education for the digital generation to become a professional generation in this digital era.  Therefore, this research aims to find the role of spirituality and religion in character formation, especially for the digital generation. This research uses a qualitative method of literature study, namely using books and other literature as the main object. The results of the study show that spirituality and religion are important factors in the formation of the character of the digital generation, namely a generation that can know the essence of its creation, formulate the purpose and meaning of life.